Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.bbrc.2015.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Electrical breakdown in tissue electroporation

Abstract: Electroporation, the permeabilization of the cell membrane by brief, high electric fields, has become an important technology in medicine for diverse application ranging from gene transfection to tissue ablation. There is ample anecdotal evidence that the clinical application of electroporation is often associated with loud sounds and extremely high currents that exceed the devices design limit after which the devices cease to function. The goal of this paper is to elucidate and quantify the biophysical and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…This phenomenon was studied on gel phantom and measured using ultrasound, magnetic resonance imaging, microphone and optical recording. The authors showed that electrical breakdown occurs across ionized electrolysis near the electrodes (mostly near the cathode), causing loud sounds, sparking and high currents [341]. …”
Section: Gene Electrotransfer – In Vivo Aspectsmentioning
confidence: 99%
“…This phenomenon was studied on gel phantom and measured using ultrasound, magnetic resonance imaging, microphone and optical recording. The authors showed that electrical breakdown occurs across ionized electrolysis near the electrodes (mostly near the cathode), causing loud sounds, sparking and high currents [341]. …”
Section: Gene Electrotransfer – In Vivo Aspectsmentioning
confidence: 99%
“…However, these applications require direct contact between the applicator, electrodes and the biological sample. Therefore, despite many applications, the methodology has considerable limitations such as the dependence of PEF distribution on the dielectric properties of the sample (Corovic et al, 2013; Peyman et al, 2015; Campana et al, 2016a; Liu et al, 2016), presence of electrochemical reactions in the electrode-electrolyte or tissue interfaces (Pataro et al, 2015) and the possibility of electrical breakdown between the electrodes (Guenther et al, 2015; Rubinsky et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…We believe that the effect we observed is related to the electrical discharge across electrolytically produced layer of gas around the electrodes. We have shown in (Guenther et al, 2015) that the electrical discharge across this layer of gas plays a major contribution to the observed violent motion of the electroporated object. We have also shown that this motion occurs primarily during the later pulses in a series of pulse experiments, when the electrolytically produced gas layer becomes substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Every clinical electroporation protocols, reversible or irreversible, generates some products of electrolysis, and some heat (Turjanski et al, 2011; Maglietti et al, 2013). We have recently shown that if substantial amounts of products of electrolysis are inadvertently generated during an electroporation protocol, a highly detrimental electrical discharge across the layer of gas formed on the electrodes can occur (Guenther et al, 2015). …”
Section: Introductionmentioning
confidence: 99%